Pengaruh Lokasi Usaha terhadap Keputusan Pembelian pada Usaha Cafe & Resto Tomyam 59 di Sipolu-Polu Kecamatan Panyabungan Kabupaten Mandailing Natal - Mutiah Pulungan; Rizka Ar Rahmah; Sari Fitri (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The aim of this research is to determine the influence of business location on purchasing decisions at Tomyam 59 Cafe & Resto. To achieve this aim, research was conducted using samples from 99 Tomyam 59 consumers using the purposive sampling method. Data collection techniques using observation, documentation and questionnaires. Data analysis methods are validity, reliability, normality, heteroscedasticity, simple linear regression, hypothesis testing, namely the t test and R square test. All tests were carried out using the SPSS Version 21 program. The results of this research show that there is an influence of business location on purchasing decisions in Sipolu-polu, Panyabungan District, Mandailing Natal Regency. Indicated by a significant value of t 0.000 which is smaller than sig = 0.005 (0.000 < 0.05) the value of R = 0.676 and R Square = 0.457 means that the business location is able to explain the dependent variable or consumer buyer decision of 0.457 × 100% = 45.7 % while another 54.3% is explained by other variables. Based on the research results, it can be concluded that business location has a positive and significant effect on purchasing decisions with a value of tcount < ttable or tcount > ttable (9.030 < 1.664 or 9.030 > 1.664). And business location has a strong relationship with purchasing decisions of 0.680.